2020
DOI: 10.1080/09585192.2020.1799234
|View full text |Cite
|
Sign up to set email alerts
|

Engaging leadership and work engagement as moderated by “diuwongke”: an Indonesian study

Abstract: The current study investigates engaging leadership and work engagement among Indonesian employees and the role of diuwongke (Javanese-Indonesian term for employees' perception of their leaders treating them with dignity and respect at work) plays in this relationship. We also included transformational leadership in order to show the added value of the novel concept of engaging leadership. Data were collected from 607 Indonesian employees working in one of the largest Indonesian state-owned companies in an agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 62 publications
0
33
0
3
Order By: Relevance
“…For example, a study among Australian employees found that engaging and transformational leadership each loaded on a separate factor instead of collapsing into one common factor (Smith, 2018 ). Furthermore, another study showed that both engaging and transformational leadership explained independently from each other similar amounts of variance of work engagement of Indonesian employees (Rahmadani and Schaufeli, 2020 ).…”
Section: The Concepts Of Work Engagement and Engaging Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study among Australian employees found that engaging and transformational leadership each loaded on a separate factor instead of collapsing into one common factor (Smith, 2018 ). Furthermore, another study showed that both engaging and transformational leadership explained independently from each other similar amounts of variance of work engagement of Indonesian employees (Rahmadani and Schaufeli, 2020 ).…”
Section: The Concepts Of Work Engagement and Engaging Leadershipmentioning
confidence: 99%
“…Employees' perception of engaging leadership can be measured using a short self-report questionnaire consisting of three items for each of the four aspects; the Engaging Leadership Scale (ELS; see Appendix). Several studies using confirmatory factor analysis confirmed that the ELS contains four components: inspiring, facilitating, strengthening, and connecting (Rahmadani and Schaufeli, 2020;Rahmadani et al, 2020a;Nikolova et al, 2021). However, these components are so closely related that, practically speaking, it is more convenient to use the total score of the ELS.…”
Section: The Measurement Of Engaging Leadershipmentioning
confidence: 99%
“…On the contrary, another study found that only PsyCap positively correlated with employee's Work Engagement, while a positive leadership style had a non-significant effect (Pugar and Parahyanti, 2018). Some studies also found that when combined with other engaging leadership and organizational culture, the positive leadership style (i.e., Transformational Leadership) still contributed a positive impact on Work Engagement (Arifin et al, 2014;Rahmadani and Schaufeli, 2020). Without considering the role of job resources such as organizational support and positive leadership styles, PsyCap showed a positive impacted on Work Engagement (Percunda and Putri, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although Work Engagement tends to be consistent across different cultures and contexts (Klassen et al, 2012), the contribution of Authentic Leadership and PsyCap as the antecedents of Work Engagement might not always be consistent. In Indonesia, positive leader behaviors could have improved Work Engagement (Arifin et al, 2014;Rahmadani and Schaufeli, 2020;Wirawan et al, 2020). However, employees might also need different resources to deal with day-to-day work demands .…”
Section: Introductionmentioning
confidence: 99%
“…Many works are devoted to engaging and inspiring leadership, which is especially relevant in the context of crises, uncertainty and unpredictability, and increased stress factors. For example, in the works of the authors Rahmadani and Schaufeli (2020), one can see positions on the need for leadership, the tools of which are the involvement of employees in innovative processes.…”
Section: Analysis Of Available Researchmentioning
confidence: 99%